Incentives and the Design of Charitable Fundraisers: Lessons from a Field Experiment - Jeffrey P. Carpenter; Peter Hans Matthews (Institute for the Study of Labor (IZA), 2015)
There has been little systematic study of the mechanisms typically used to raise money for charity. One of the most common is the simple raffle in which participants purchase chances to win a prize at a constant price. We conduct a field experiment randomly assigning participants to four raffle treatments to examine the effectiveness of alternative incentive schemes designed to encourage either participation or volume. Our results confirm the importance of incentives in that we find revenue gains are available on both margins. Our experiment, and others like it, illustrates the power of field experiments to inform fundraising choices.
Keywords: H41; D03; D64; C93; 330; philanthropy; fundraising; incentives; public good; raffle; Tullock contest; field experiment